Effectiveness and Tolerability of a Standardized Extract from Ageratina pichinchensis in Patients with Diabetic Foot Ulcer: A Randomized, Controlled Pilot Study - Romero-Cerecero, Ofelia; Zamilpa, Alejandro; Tortoriello, Jaime (Planta Medica, 2015)
Previous works have shown that extracts obtained from Ageratina pichinchensis are capable of reducing the time needed for wounds to heal. By means of a randomized, double-blind pilot study, the objective of this work was to evaluate the effectiveness and tolerability of a phytopharmaceutical developed with a standardized extract (5 %, cream formulation) of A. pichinchensis, topically administered in patients with diabetic foot ulcer. Micronized silver sulfadiazine (1 %) was employed as a control treatment. Treatments were randomly assigned to each patient, and clinical evolution was evaluated weekly until complete healing of the wound. All patients who concluded the study achieved complete healing of their ulcers. After six weeks of treatment, patients in the experimental group exhibited a wound-healing process of 77.5 %, while that of patients in the control group was 69.8 %. A statistically significant difference was not found between groups. The average time needed for complete wound healing was 65.47 ± 47.08 days for patients treated with the A. pichinchensis extract and 77.46 ± 50.8 days for patients in the control group (p = 0.509). There was no case in either of the groups in which adverse side effects were identified. Thus, it was concluded that the A. pichinchensis extract showed the ability to improve the healing process in patients with diabetic foot ulcer; however, no statistically significant differences were observed when compared with results obtained in patients administered the control treatment (micronized silver sulfadiazine). Some limitations of this study must be addressed, such as small sample size. This work comprises a pilot study that could be useful in a future clinical trial with a greater number of patients.
Keywords: Ageratina pichinchensis; Asteraceae; diabetic foot ulcer; wound healing; diabetes